Optically stimulated luminescence in Ag doped Li2B4O7 single crystal and its sensitivity to neutron detection and dosimetry in OSL mode. (May 2016) - Patra, G.D.; Singh, S.G.; Tiwari, B.; Singh, A.K.; Desai, D.G.; Tyagi, M.; Sen, S.; Gadkari, S.C.
Abstract: Optically stimulated luminescence (OSL) measurements have been carried out on single crystals of Ag doped Li2 B4 O7 (LTB:Ag) after exposure to various nuclear radiations. The time integrated OSL intensity is found to be linear in the range from 0.1 Gy to 500 Gy. Fading of the OSL signal was found to be around 36% in 48 h. The presence of 6 Li and 10 B has been gainfully utilized to measure doses of thermal neutrons. Further, the large difference between the wavelength of the stimulation source (∼460 nm) and emission from the LTB:Ag at 270 nm has enhanced the signal-to-noise ratio in a simple OSL set-up with suitable filters. The high sensitivity of the LTB:Ag to thermal neutrons will be useful in variety of applications including personal dosimetry in mixed-fields and imaging devices for neutron radiography. Highlights: Li2 B4 O7 :Ag single crystals are grown by the Czochralski technique. Li2 B4 O7 :Ag single crystals are investigated using TSL, OSL techniques. These crystals are found promising for OSL dosimetry.